Retos de género ante el retorno al trabajo - Corlett, S. (Buenas prácticas para la gestión preventiva desde la perspectiva de género: Guía de autodiagnóstico, 2025)
This manual compiles contributions from Work and Organizational Psychology to the promotion of health and workplace well-being, considering a gender perspective in addressing psychosocial risks. This perspective is prominently emphasized in the draft of the new Occupational Risk Prevention Law, particularly regarding the prevention of psychosocial risks, workplace well-being, and health. Best practices are outlined, and a Gender Perspective Integration Diagnosis Guide (DIGEN Guide) is included, covering ten specific areas: physical health and workplace safety, psychological well-being, mental health, return to work, violence and harassment, work-life balance, teleworking, vertical and horizontal segregation, diversity and intersectionality, and inclusive leadership.